PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR TENAGA KEPENDIDIKAN DI SD NEGERI 148 KECAMATAN LIMUN KABUPATEN SAROLANGUN - Tetty Asnawi; Nasta Trilaksmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Human resources development is imperative to confront the present task and to answer the challenges of the future. An organization can survive and grow if the Organization has the human resources that individually have the ability and the will to accomplish every task with full responsibility. Ability and willingness to work will not grow by itself, but the organization is obligated to have the system development and coaching against its members in planning. This research aims to know the influence of education and training towards the development of the careers of produce educators in SD N 148 kec. Lemonade kab. Sarolangun partially. Based on statistical tests can noted that there was significant influence between the training towards the development of produce educators career at SD N 148 sarolangun Regency lemonade subdistrict is evidenced by the value of fhitung ˃ ftabel 5.698 2.243.Keyword: training, career development, workforce education